A corpus analysis of non-contiguous phraseological patterns in the discussion section of microeconomics research articles - Ang, Leng Hong (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the non-contiguous phraseological profile of Microeconomics research articles, specifically focusing on key lexical frames within the Discussion section. Key lexical frames are non-contiguous recurrent expressions with variable slots unique to specific contexts such as genres or disciplines. The analysis is based on a corpus of Discussion sections from research articles published in four leading Microeconomics journals between 2017 and 2022. Using the KfNgram program, four-word lexical frames were identified and refined according to exclusion criteria. The resulting list of lexical frames was compared with a general corpus, the Corpus of Contemporary American English, yielding 43 four-word key lexical frames unique to Microeconomics. These frames were analysed following the structural classification by Gray and Biber (2013) and the functional taxonomy by Simpson-Vlach and Ellis (2010). Structurally, most key lexical frames were found to be function word frames, while functionally, they primarily served referential functions. The findings reveal significant phraseological variation, encompassing both lexical and grammatical constructions unique to the field of Microeconomics. These insights contribute to a deeper understanding of discipline-specific academic writing and have important implications for English for Academic Purposes pedagogy. In particular, this research aims at improving the learners’ part-genre awareness and competence. By identifying and analysing key lexical frames, the study provides valuable resources for enhancing the teaching of academic writing in Microeconomics, particularly for non-native English speakers.